Explosive morning growth phenomena of NH3 on the North China Plain: Causes and potential impacts on aerosol formation. (February 2020) - Kuang, Ye; Xu, Wanyun; Lin, Weili; Meng, Zhaoyang; Zhao, Huarong; Ren, Sanxue; Zhang, Gen; Liang, Linlin; Xu, Xiaobin
Abstract: Atmospheric ammonia (NH3 ) as the most important alkaline gas in the atmosphere has attracted much attention in recent years due to its critical role in haze formation, especially on the North China Plain (NCP). Comprehensive studies are needed for investigating diurnal variations of NH3 and underlying mechanisms in different seasons and their potential impacts on atmospheric chemistry. In this study, continuous long-term observation (Mar. 2016 to May 2017) of NH3 at a rural site in the NCP was used to characterize the diurnal variation of NH3 in different seasons and to unveil its causes and potential impacts on atmospheric chemistry. NH3 concentrations displayed rapid increases during the morning, reaching very prominent peaks mostly between 8:00 to 11:00 LT. Such frequent (55%) morning peaks were mainly caused by the evaporation of dew and guttation water droplets. Average dew and guttation water volume concentrations of 750 mL m −2 was estimated for spring, which resulted in approximate NH3 emissions of 800 ng m −2 s − 1 . Such high emission fluxes from dew and guttation water evaporation have never been reported before, suggesting dew and guttation droplets to be significant night-time reservoirs and strong morning sources for NH3 . In light of recent studies putting forward that NH3 can promote the heterogeneous formation of HONO and nitrate under high humidity conditions, we investigated the differences in HONO and aerosol chemical composition diurnal variations between days with and without NH3 morning spikes during November. HONO, nitrate and sulfate concentrations were significantly higher for days with NH3 morning spikes, with HONO displaying a morning peak near that of NH3 . These results demonstrate that the prevailing NH3 morning spikes on the NCP have significant influences on aerosol formation and atmospheric chemistry. NH3 emission mitigation strategies and regulations are urgently needed. Highlights: Highly frequent morning peaks of NH3 caused by dew and guttation water. Dew and guttation water exhibit very high NH3 storage and emission capacity. NH3 diurnal variation has potential impact on rapid haze formation. Abstract : Dew and guttation water exhibit very high NH3 storage and emission capacity, causing highly frequent NH3 morning peaks, inducing rapid haze formation in the North China Plain.